Two-Step Solid Lipid Extrusion as a Process to Modify Dissolution Behavior - Windbergs, Maike (Springer US, 2010)
Extrudates based on varying ratios of the triglyceride tripalmitin and the hydrophilic polymer polyethylene glycol as matrix formers were produced as oral dosage forms with controlled release characteristics. The extrudates were processed below the melting points of the excipients and contained the hydrophobic model drug chloramphenicol. The influence of the ratio of the matrix formers on drug dissolution was investigated, with an increase in the water-soluble polymer content increasing the drug release rate. In addition, the effect of varying the extrusion process on the extrudate structure and drug dissolution was investigated. Two-step extrusion was performed, which comprised an initial extrusion step of drug and one matrix component followed by milling these extrudates and a second extrusion step for the milled extrudates mixed with the second matrix component. Initial extrusion with polyethylene glycol led to increased dissolution rates, while initial extrusion with tripalmitin led to decreased dissolution rates compared to the dissolution characteristics of extrudates containing the same composition produced by one-step extrusion. Thus, two-step solid lipid extrusion can successfully be used as a process to modify the dissolution behavior of extrudates.